The Theoretical And Pedagogical Foundations Of Socialization In Personal Development (Eurasian Research Bulletin, 2025)
This article analyzes the theoretical and pedagogical foundations of socialization in the process of personal development. It examines the meaning and historical formation of the concept of “socialization” through sociological, psychological, and pedagogical interpretations. The article explores the roles of family, school, and society in the socialization process, as well as mechanisms for fostering civic consciousness through education and upbringing. International experiences (Finland, Japan, USA) and current reforms in Uzbekistan are discussed. The effectiveness of activity-based learning, cooperative methods, and learner-centered approaches in developing personal social activity is substantiated